2018
DOI: 10.1002/hbm.24282
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of a multimodal marker of major depressive disorder

Abstract: This study aimed to identify biomarkers of major depressive disorder (MDD), by relating neuroimage-derived measures to binary (MDD/control), ordinal (severe MDD/mild MDD/control), or continuous (depression severity) outcomes. To address MDD heterogeneity, factors (severity of psychic depression, motivation, anxiety, psychosis, and sleep disturbance) were also used as outcomes. A multisite, multimodal imaging (diffusion MRI [dMRI] and structural MRI [sMRI]) cohort (52 controls and 147 MDD patients) and several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 140 publications
3
27
1
1
Order By: Relevance
“…Imaging data and neurobiological data were included in the data fusion. In both studies, the results did not show strong support for the hypothesis and did not provide sufficient evidence for the sought biomarkers [160, 161] .…”
Section: Multimodal Imaging Data Fusion: Diseasesmentioning
confidence: 69%
See 1 more Smart Citation
“…Imaging data and neurobiological data were included in the data fusion. In both studies, the results did not show strong support for the hypothesis and did not provide sufficient evidence for the sought biomarkers [160, 161] .…”
Section: Multimodal Imaging Data Fusion: Diseasesmentioning
confidence: 69%
“…Among the methods of the multimodal MRI image fusion in depressive disorders, support vector machine (SVM) [160] and linked independent component analysis [161] was recently used, respectively, to identify biomarkers for the classification and prediction of symptom loads of heterogeneous MDD cohorts. Imaging data and neurobiological data were included in the data fusion.…”
Section: Multimodal Imaging Data Fusion: Diseasesmentioning
confidence: 99%
“…This all suggests a more complex relationship between SSRIs, sleep, and treatment response that demands further investigation. Furthermore, it seems that the predictability of changes in insomnia related to depression is either specific to FC or the influence of citalopram, since this factor could not be predicted in a well-powered study using structural and diffusion MRI (Yang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The left IFG-tri has been associated with language processing and emotional processing. Studies of depression and non-depressed control subjects found that IFG-tri was one of four areas that contributed significantly to discriminating between the two groups (Yang et al, 2018), with greater cortical thinning in the left IFG-tri in the depressed group (Na et al, 2016), and volume reductions of the left IFG-tri in the depressed group were associated with a particular genetic polymorphism (Han et al, 2017). As left IFG-tri comprises the Broca's area, our results also raise the possibility that inner speech or self-referential dialogue may play an important role in depression.…”
Section: Discussionmentioning
confidence: 99%